Rehabilitation of patients with arthrosis and hip joint injuries - M. M. Taylashev; P. P. Salatin; I. G. Motorina (Acta Biomedica Scientifica)
The authors studied remote results in 236 (83,7 %) of 282 patients who had hip replacement. 195 (82,6 %) patients had good results, 38 (16,2 %) - satisfactory, 2 (0,84 %) - unsatisfactory (due to the development of suppurative complications). Lethal outcome was registered in 1 (0,8 %) case (myocardial infarction). 16 patients had bilateral hip replacement. Authors divided rehabilitation measures into local (aimed to the restoration of limb's functions) and general and also by the periods. Precise compliance with standards at the endoprosthesis replacement with further optimal selection of specific physical factors and exercise therapy allow to recover patient to active and qualitative life.